2018
DOI: 10.1186/s12960-018-0290-z
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional team member’s satisfaction: a mixed methods study of a Chilean hospital

Abstract: IntroductionThe health organizations of today are highly complex and specialized. Given this scenario, there is a need for health professionals to work collaboratively within interprofessional work teams to ensure quality and safe care. To strengthen interprofessional teamwork, it is imperative that health organizations enhance strategic human resources management by promoting team member satisfaction.ObjectiveTo analyze the satisfaction of members in interprofessional teams and to explore interpersonal relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 47 publications
0
20
1
11
Order By: Relevance
“…Other studies have shown that job satisfaction is associated with interprofessional perspective,37 team climate,38 and organisational culture and teamwork 39 40. While a number of previous studies have demonstrated that organisational culture is important for IPC,41 42 we found that relationships with neighbouring facilities were more strongly associated with IPC than the hospital to which participants belonged in multiple regression analysis.…”
Section: Discussioncontrasting
confidence: 53%
“…Other studies have shown that job satisfaction is associated with interprofessional perspective,37 team climate,38 and organisational culture and teamwork 39 40. While a number of previous studies have demonstrated that organisational culture is important for IPC,41 42 we found that relationships with neighbouring facilities were more strongly associated with IPC than the hospital to which participants belonged in multiple regression analysis.…”
Section: Discussioncontrasting
confidence: 53%
“… 4 Reviews of interprofessional communication have reported the presence of a relationship between patient outcomes and healthcare communication. 5 6 Many studies, however, focus on individual–profession relationships or organisational climates in communication, 7 8 whereas studies on clinical network structures are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Neste sentido, quatro dimensões podem ser identificadas: participação segura para comunicar e interagir com a equipe; apoio à inovação; clareza dos objetivos e orientação com compromisso no desenvolvimento das tarefas (7) . Estudos evidenciam correlação positiva entre o CTE e a dinâmica de trabalho (8) , relação de confiança entre os médicos e usuários (9) , satisfação dos profissionais (10) e usuários (11) , eficiência no cuidado (12) e qualidade no cuidado para inovação (13)(14) .…”
Section: Introductionunclassified